'Marks of true sportsmanship' : the conceptions of sportsmanship in Singapore from colonial era to present day - Hong, Benjamin Kay Sheng (Nanyang Technological University, 2021)
Singapore’s sporting scene has been revitalised by Joseph Schooling’s recent Olympic success, being the first Singaporean clinching a gold medal. Schooling calls for more financial support as he considered funding to be one of the concerns holding back Singaporean athletes. Schooling’s views on sport are a contrast to older Singaporean athletes, such as Tan Eng Liang. Tan believes that material gain, and monetary incentive should be aside from sports, and that representing the country was incentive enough. However, both athletes have the nation at heart, prioritising national pride and glory. Nonetheless, they still differ in opinion despite their common nationality and sentiments of patriotism. My thesis seeks to explain the differences in conceptions of sportsmanship between generations through the examination of the various influences and values that affect such conceptions.